Trends in Surgical Management of Esophageal Cancer - Thakur, Binay; Devkota, Mukti; Thapa, Asha (Journal of Nepal Health Research Council, 2023)
Background: Management of esophageal cancer has changed to a combined modality approach over the past two decades due to poor outcome. Recently, multimodal treatment has become the standard practice. The aim of this study was to evaluate the changing trends in management and outcomes of esophagectomy over 15 years from a single center in Nepal. Methods: Patients with squamous cell carcinoma and adenocarcinoma of esophagus/ gastroesophageal junction who underwent surgery between 2001-2018 were analyzed. Patients were grouped into three successive 5-year periods. Results: 547 patients underwent esophagectomy during 2001-2018. There was increased trend of neoadjuvant treatment from 9-13% to 52% (p<.001) and minimally invasive surgery (MIS) from 0% to 80% (p<.001). 30-day mortality decreased from 8% to 1% (p=.01). The 5-overall survival was 24% which increased from 17% to 27% (p=.003). Conclusions: Long term outcome has improved over last 15 years with decreasing mortality which appears to be due to incorporation of MIS and neoadjuvant treatment. Keywords: Esophagectomy; esophageal cancer; multimodality therapy